2011
DOI: 10.1161/circresaha.111.248880
|View full text |Cite
|
Sign up to set email alerts
|

miR-15 Family Regulates Postnatal Mitotic Arrest of Cardiomyocytes

Abstract: Rationale Mammalian cardiomyocytes withdraw from the cell cycle during early post-natal development, which significantly limits the capacity of the adult mammalian heart to regenerate following injury. The regulatory mechanisms which govern cardiomyocyte cell cycle withdrawal and binucleation are poorly understood. Objective Given the potential of microRNAs (miRNAs) to influence large gene networks and modify complex developmental and disease phenotypes, we searched for miRNAs that were regulated during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
412
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 406 publications
(430 citation statements)
references
References 45 publications
11
412
1
6
Order By: Relevance
“…Results of this study showed that the expression of miR‐195 was increased in older SkMs but decreased during the induction of de novo reprogramming of old SkMs into iPSCs. Although previous studies have demonstrated that miR‐195 is associated with cardiac hypertrophy and heart failure by controlling cell cycle‐related genes that affect aging (Porrello et al ., 2011), we hypothesized that upregulated miR‐195 is a senescence‐associated miR in reprogramming. Intriguingly, there was an observed discrepancy between miR‐195 and SA‐β‐gal expression in early passaged old SkMs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study showed that the expression of miR‐195 was increased in older SkMs but decreased during the induction of de novo reprogramming of old SkMs into iPSCs. Although previous studies have demonstrated that miR‐195 is associated with cardiac hypertrophy and heart failure by controlling cell cycle‐related genes that affect aging (Porrello et al ., 2011), we hypothesized that upregulated miR‐195 is a senescence‐associated miR in reprogramming. Intriguingly, there was an observed discrepancy between miR‐195 and SA‐β‐gal expression in early passaged old SkMs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The most shared miRNAs are endothelial cell (EC) derived and include miR‐126/17–92/15/34 clusters as representing highly circulating miRNAs 2, 3, 4, 5, 6.…”
Section: Differentially Expressed Mirnas Act As Switchers or Fine‐tunersmentioning
confidence: 99%
“…The miR‐15 and ‐34 families exert tumour suppressor activity in multiple adult tissues 4, 5, 28, 33. In clinical studies on patients with CVD, the anti‐atherosclerotic and vasodilatation effects of statins have been addressed to induce the bioactivity of NOS and Bcl‐2 in endothelium.…”
Section: Ischaemia/hypoxia‐associated Mirna Signatures In Atherosclermentioning
confidence: 99%
See 2 more Smart Citations